Coloring of egg yolks of laying hens fed with sorghum-based feed with addition of natural and synthetic pigments - Miranda, Diogo Alvarenga; Valentim, Jean Kaique; Oliveira, Helder Freitas de; Chaves, Claudiane Aparecida Rocha; Geraldo, Adriano; Machado, Luiz Carlos; Mendes, Janaína Palermo; Almeida, Alexander Alexandre (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to evaluate the inclusion of synthetic pigment (Cantaxanthin 10%) combined with levels of natural and synthetic pigment supplementation in the diet of commercial laying hens in diets based on sorb. We used 150 commercial laying hens with 67 weeks of age of the Hisex Brown strain, distributed in a completely randomized design with five treatments, six replicates of five birds/repetition. The treatments evaluated were: 25 g/t carophyll yellow 10% + 20 g/t red carophyll (T1); 300 g/t of Marigold 2% + 10 g/t of Cantaxanthin 10% (T2); 300 g/t of Marigold 2% + 20 g/t of Cantaxanthin 10% (T3); 300 g/t of Marigold 2% + 30 g/t of Cantaxanthin 10% (T4); 300 g/t of Marigold 2% +20 g/t red carophyll (T5). The Tukey test was applied at the level of 5% probability for the various performance and quality of eggs. There was a difference between treatments only for yolk staining, where the increase in color was reflected according to the increase in pigmenting levels in the diets, and the other variables were not affected. The supplementation level of 300 g.t-1 of natural yellow pigment + 30 g.t-1 of industrial red pigment in diets based on sorb for laying hens provided better yolk color index.